Development of Android-Based Learning Application Using Articulate Storyline 3 - Pance Ronaldi Solo; Juliana M.H Nenohai; Ofirenty Elyada Nubatonis (Program Studi Tadris Matematika Universitas Islam Negeri (UIN) Salatiga, 2023)
This research aims to create an Android-based learning application assisted by Articulate Storyline 3 software for class VIII students of SMP Negeri 13 Kupang that is valid, practical, and effective. The method used is Research and Development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. Data collection techniques and instruments include interviews, questionnaires, and tests. The data analysis technique uses qualitative and quantitative descriptive analysis techniques. This research produces an Android-based application product named